2005
DOI: 10.1016/j.orthres.2005.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of hedgehog signaling peptides in naturally acquired equine osteochondrosis

Abstract: Hypertrophic differentiation and endochondral ossification of growth cartilage are regulated by a complex array of signaling peptides, including parathyroid hormone-related protein (PTH-rP), Indian hedgehog (Ihh), and bone morphogenetic proteins (BMPs). This study investigated the expression of Ihh, Patched1 and 2 (Ptcl, Ptc2), Smoothened (Smo), Glil, and Gli3, in naturally acquired articular osteochondrosis, using an equine model. Cartilage was harvested from osteochondrosis (OC) affected femoropatellar or sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
(33 reference statements)
1
33
1
1
Order By: Relevance
“…Runx2 is normally expressed in proliferating and hypertrophic chondrocytes in the growth plate, with highest expression in terminal hypertrophic chondrocytes. 5 Runx2 induces genes typical of terminal chondrocyte differentiation, including type X collagen, MMP-13, and Ihh, 5,29,30 thus it is not surprising that these genes are also up-regulated in OC lesions (as demonstrated here for MMP-13, and by Semevolos et al, 2005 11 for Ihh).…”
Section: Discussionsupporting
confidence: 61%
“…Runx2 is normally expressed in proliferating and hypertrophic chondrocytes in the growth plate, with highest expression in terminal hypertrophic chondrocytes. 5 Runx2 induces genes typical of terminal chondrocyte differentiation, including type X collagen, MMP-13, and Ihh, 5,29,30 thus it is not surprising that these genes are also up-regulated in OC lesions (as demonstrated here for MMP-13, and by Semevolos et al, 2005 11 for Ihh).…”
Section: Discussionsupporting
confidence: 61%
“…In addition, PTCH2 splice variants were able to reconstitute a Dhh-dependent transcriptional response in cells lacking Ptc1 function (52). It was reported that Ptc2 and Ihh are highly expressed in equine osteochondrosis-affected cartilage and repair tissue, suggesting that Ihh-Ptc2 signaling might play a role in diseased adult cartilage (56).…”
mentioning
confidence: 99%
“…These riboprobes were previously determined to perform well on equine cartilage samples. 5,6 The probe was added to hybridization buffer containing 25% deionized formamide, 10% dextran sulfate, 300 mM NaCl, 10 mM TRIS, 1 mM EDTA, 1 Â Denhardt's solution (0.02% BSA, 0.02% Ficoll, and 0.02% polyvinylpyrrolidone), 0.5 mg yeast tRNA/mL, and 10 mM dithiothreitol. The probe (0.12 pmoles, specific activity 1.0-1.2 Â 10 7 cpm/pmol) in 40 mL of hybridization buffer was applied to a section on each slide, the slides coverslipped, and then incubated overnight in humid chambers at 438C.…”
Section: Real-time Quantitative Reverse Transcription Polymerase Chaimentioning
confidence: 99%
“…In addition, alterations in the expression of PTHrP and Ihh have been shown to occur in osteochondrosis, a disease of articular cartilage development. 5,6 Previous studies have shown that the expression of regulatory molecules in articular cartilage may change during the postnatal period. [7][8][9][10][11][12][13][14][15] Qualitative assessment of PTHrP mRNA and protein expression in postnatal rats showed decreased expression in articular cartilage from youth to maturity.…”
Section: Introductionmentioning
confidence: 99%